Respuesta :
Let u be the value of tan(x) and that the equation above may also be written as,
u² - 3u + 2 = 0
The equation can be factored as follows,
(u - 1)(u - 2) = 0
u - 1 = 0 ; u = 1 and u - 2 = 0 ; u = 2
Thus, tangent(x) = 1 and tangent(x) = 2. The values of x are 45° and 63.43°.
u² - 3u + 2 = 0
The equation can be factored as follows,
(u - 1)(u - 2) = 0
u - 1 = 0 ; u = 1 and u - 2 = 0 ; u = 2
Thus, tangent(x) = 1 and tangent(x) = 2. The values of x are 45° and 63.43°.
Answer:
x= 63.43° and x= 45°
Step-by-step explanation:
Given that
[tex] tan^2x-3 tanx +2=0[/tex]
Lets assume that
tan x =k
Now by replace tan x by k we will get
[tex]k^2-3 k +2=0[/tex]
Now above equation is a quadratic equation
[tex]k^2-2 k - k+2=0[/tex]
k(k-2)-1(k-2)=0
So k=2,k=1
Now putting tan x in place of k
tan x =2 and tan x =1
So by using inverse property
x= 63.43°
tan x =1
x= 45°